The Apostolic Penitentiary and Violence in the Roman Curia - Salonen, Kirsi (Violence and the medieval clergy, 2011)
This essay analyses the petitions brought before the Apostolic Penitentiary concerning violence committed in the papal curia during the pontificate of Pius II (1458–1464).¹ Since some readers might not be familiar with the Apostolic Penitentiary and its medieval sources, I will start by explaining briefly what the Penitentiary was and what kinds of documents its archives can offer us in respect of violence. The Apostolic Penitentiary was one of the papal offices – officially classified as one of the papal tribunals – which dealt with all the issues that concerned sins. Defining the Penitentiary as a “tribunal” is, however, slightly misleading...